A model of behavioral climate change education for higher educational institutions - Kuok Ho Daniel Tang (Environmental Advances, 2022)
This paper puts forth a novel model of Climate Change Education (CCE) targeting to bridge the attitude-behavior gap in students’ climate action, called the behavioral CCE. It refers to relevant literature retrieved through the PRISMA model to identify the determinants of behaviors and pedagogies of CCE, prior to synthesizing a model of behavioral CCE. The model proposes CCE that comprises three domains, namely the knowledge aspect, the practical CCE and the community CCE. The knowledge aspect conveys the basic concepts and modelling of climate change as well as addresses the misconceptions and biases related to climate change. Practical CCE equips students with skills related to lifecycle assessment and carbon footprint calculations while guiding them through identifying, reducing, changing and eliminating daily activities and habits contributing significantly to anthropogenic carbon emission. Community CCE enables students to make an impact on the community and motivate the community towards climate action, thus consolidating the attitude and behavioral changes resulted from the other two CCE components.